Towards sustainable construction: RCA under different crushing techniques to determine the utilisation potential index for concrete production - Venkrbec, Václav; Haond, Niels; Boel, Veerle; Nováková, Iveta (Sustainable Materials and Technologies, 2025)
The construction industry is associated with the largest contribution to global greenhouse gas emissions so as the largest consumption of natural resources and production of waste. Concrete consists of 70 % to 80 % of aggregates and that makes it also easily recyclable into reusable granular material, so-called recycled concrete aggregates (RCA), for multiple reuse purposes. RCA can be of various qualities depending on aspects like the quality of the parent concrete (PC), the ambient exposure during its service life and the crushing technology used for its production. This paper presents large-scale study focused on determining the effects of three different crushing technologies, namely jaw crusher, impact crusher and cone crusher, and their influence on the properties of produced RCA conducted with one type of PC. The investigated properties according to EU standards were particle size distribution, fines content, flakiness index, saturated and surface-dried particle density, and water absorption. Experimental tests were used to quantify the residual mortar content and the amount of unfractured NA from the PC. Moreover, properties of the PC, such as compressive strength, density, and maximum particle size of NA, were determined. In this study, multi-criteria decision analysis (MCDA) is used to establish a new index, the utilisation potential index (UPI), to assess the applicability of crushed RCA. Results showed that the cone crusher produces 26.3 % and 21.4 % more fraction 8–22.4 mm than the impact, respectively, jaw crusher but with a slightly lower UPI, which makes those RCA more suitable for conventional concrete rather than high-strength concrete. Conversely, the RCA fraction 0–4 mm produced by a cone crusher has a significantly better UPI than the same fraction produced by the other tested crushers. At the end of the paper, conclusions based on both the relationship between RCA properties and crusher type as well as the relation of RCA to PC properties are presented, evaluated, and discussed. The case study is aligned with an experimental framework which is beneficial in the decision-making process to determine the most suitable crusher type for the desired RCA application. The paper contributes to a greater focus on the method of concrete production and may be considered valuable by other researchers, as well as by producers of recycled aggregates and concrete producers in the near future. •Real-case study of deconstruction and recycling of 6.40 m3 from one source, a concrete harbour pier.•3 types of widely used crushers: jaw, impact and cone crusher (each 2.13 m3).•Jaw and impact crushers produce higher quality coarse RCA by removing most mortar.•Cone crusher produced the high share of coarse aggregates with lower quality.•The new Utilisation Potential Index (UPI) was introduced and its applicability was demonstrated.